Dynamic relationship between sukuk and economic growth in Indonesia: Evidence from Vector Error Correction Model (VECM) and Wavelet Analysis - Novitasari, Elva; Arundina, Tika (Universitas Negeri Surabaya, 2023)
This research highlights the positive development of the sukuk market in Indonesia, particularly corporate sukuk and sovereign sukuk. Sovereign sukuk experienced faster growth, despite corporate sukuk being issued earlier. Corporate sukuk is considered an economic stimulus through corporate capital expenditure, while sovereign sukuk is used for infrastructure financing. Both types of sukuk are expected to drive economic growth, although the role of sukuk in economic growth is still debated. Therefore, research under current conditions remains highly relevant. This study employs the Vector Error Correction Model (VECM). The findings indicate a positive contribution of sukuk to long-term economic growth, and economic growth has a positive impact on the sukuk market in the short term. Impulse Response Function (IRF), Variance Decomposition (VD), and Granger Causality analyses are utilized to measure the influence and causality of variables. The impact of sovereign sukuk on economic growth, including the period during the Covid-19 pandemic, has increased compared to the pre-pandemic period. Wavelet analysis is also employed to explore the movements of retail and non-retail sovereign sukuk concerning economic growth in various time periods. The movements of retail sovereign sukuk may serve as an indication of economic growth, and a strong correlation is found between retail sovereign sukuk and economic growth.